Kepribadian Tokoh dalam Novel Perempuan yang Menangis Kepada Bulan Hitam Karya Dian Purnomo - Lillah, Farah Hayaatan; Sutejo, Sutejo; Munifah, Siti (STKIP PGRI Ponorogo Press, 2024)
This research aims to describe the character>s personality from the perspective of human personality structure, using a literary psychology approach. This research is a qualitative descriptive study. The data collection technique in this research uses reading and note-taking techniques. The object used in this research is the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo, published by Gramedia Pustaka Utama in 2020. This novel tells the story of the character Magi Diela>s struggle to escape the customs that bound her to become an old man>s wife, named Leba Ali. The results of this research are the personalities of the characters Magi Diela and Leba Ali which are influenced by their personality structure, namely the id, ego and superego, which are analyzed using the psychological theory of personality initiated by Sigmund Freud.